Malarial Pigment Hemozoin and the Innate Inflammatory Response - Olivier, Martin; Van Den Ham, Kristin; Shio, Marina T.; Kassa, Fikregabrail A.; Fougeray, Sophie (Frontiers in Immunology, 2014)
Malaria is a deadly infectious disease caused by the intraerythrocytic protozoan parasite Plasmodium. The four species of Plasmodium known to affect humans all produce an inorganic crystal called hemozoin (HZ) during the heme detoxification process. HZ is released from the food vacuole into circulation during erythrocyte lysis, while the released parasites further infect additional naive red blood cells. Once in circulation, HZ is rapidly taken up by circulating monocytes and tissue macrophages, inducing the production of pro-inflammatory mediators, such as interleukin-1β (IL-1β). Over the last few years, it has been reported that HZ, similar to uric acid crystals, asbestos and silica, is able to trigger IL-1β production via the activation of the NOD-like receptor containing pyrin domain 3 (NLRP3) inflammasome complex. Additionally, recent findings have shown that host factors, such as fibrinogen, have the ability to adhere to free HZ and modify its capacity to activate host immune cells. Although much has been discovered regarding NLRP3 inflammasome induction, the mechanism through which this intracellular multimolecular complex is activated remains unclear. In the present review, the most recent discoveries regarding the capacity of HZ to trigger this innate immune complex will be discussed, as well as the impact of HZ on several other inflammatory signalling pathways.